Non-equilibrium electron and vibrational distributions under nanosecond repetitively pulsed CO discharges and afterglows: II. the role of radiative and quenching processes. (13th September 2018) - Pietanza, L D; Colonna, G; Laricchiuta, A; Capitelli, M
Abstract: The non-equilibrium vibrational distributions and electron energy distributions of CO in nanosecond repetitively pulsed discharges and afterglows have been determined from a coupled solution of the time-dependent Boltzmann equation for the electron energy distribution function (eedf) of free electrons, the master equations for vibrational levels of CO and the electronic excited states of CO, O and C atoms. The optically thick plasma conditions have been investigated in a companion paper (part I), while in the present paper we also show the results obtained by allowing radiative emission processes (optically thin plasma) as well as electronic excited state collisional quenching processes. Two case studies, which differ for the duration of the afterglow following each pulse (1 μ s and 25 μ s case studies) are discussed, and each pulse is characterized by a time-dependent electric field profile in the range 0–20 ns. The results, which depend on the number of pulses considered in the discharge and the corresponding afterglow duration, show several peaks in the eedf due to super-elastic electronic collisions. On the other hand, the quenching process of the a 3 Π electronic state of CO determines the pumping of vibrational quanta in the v  = 27 level, which in turn largely modifies the vibrational distribution function (vdf) of CO. As a consequence, the quenching of the a 3 Π state increases the reactivity of CO through the Boudouard reaction, and under given conditions, this channel can become more important than the dissociation rates by electron impact collisions.